Panoramic Radiomorphometric Indices of the Mandible in an Iranian Population - Tafakhori, Zahra; Nejati, Hadi (Journal of Dental School, 2019)
Objectives: Radiomorphometric indices measured on simple radiographic images can be used for qualitative and quantitative assessment of bone. Panoramic radiographic imaging can therefore assist dentists in early detection of osteoporosis in patients. Considering the effect of ethnic and environmental factors on development of osteoporosis and absence of normal values of radiomorphometric indices for the Iranian population, which results in use of normal values of other ethnicities for determining the presence or absence of osteoporosis in patients, the present study was conducted to evaluate radiomorphometric indices in patients presenting to a private oral and maxillofacial radiology clinic in Rafsanjan, Iran. Methods: The present cross-sectional study examined 385 eligible patients who met the inclusion criteria. Their demographic characteristics including age, gender and level of education were recorded. Their panoramic radiographic data, including radiomorphometric indices such as mandibular cortical index (MCI), antegonial index (AI), and gonial index (GI), were evaluated on each image. Multiple logistic regression was used to evaluate the effect of variables on mandibular bone radiomorphometric indices. P-value less than 0.05 was considered statistically significant. Results: The mean AI and GI were 2.19±0.56 and 0.87±0.31mm, respectively. In assessment of MCI, since none of the patients fell under the C3 category, all patients were categorized as C1 or C2. Assessment of demographic variables and radiomorphometric indices showed that age had a significant relationship with MCI and AI while gender had a significant relationship with GI. Conclusion: Radiomorphometric indices can be used to assess the risk of osteoporosis in patients.